Climate-Smart Agriculture in Chad - International Center for Tropical Agriculture; International Crops Research Institute for the Semi-Arid Tropics; Food and Agriculture Organization of the United Nations; World Bank; Jaquet, Stéphanie; Houessionon, Prosper; Patallet, Bianpambe; Beassemda, Lydie; Giles, James; Gonzales, Carlos; Otieno, Mary; Kinyua, Ivy Wambui (2021)
The climate-smart agriculture (CSA) concept reflects an ambition to improve the integration of agriculture development and climate responsiveness. CSA aims to achieve food security and broader development goals under a changing climate and increasing food demand. CSA initiatives can sustainably increase productivity, enhance resilience, and reduce/remove greenhouse gases (GHGs), but require planning to address trade-offs and synergies between the three CSA pillars, namely: productivity, adaptation, and mitigation(1). The priorities of different countries and stakeholders can converge towards achieving more efficient, effective, and equitable food systems that address challenges in environmental, social, and economic dimensions across productive landscapes. While the CSA concept is new, and still evolving, many of the practices that make up CSA already exist worldwide and are used by farmers to cope with different types of production risks(2). Mainstreaming CSA requires critical stocktaking of ongoing and promising practices for the future, and of institutional and financial enablers for CSA adoption and scaling. This country profile provides a snapshot of a baseline created to initiate discussions on entry points for investing in CSA at scale in Chad.